Peran Orang Tua Dalam Pengawasan Penggunaan Teknologi Digital Pada Anak - Ervina Anatasya; Linda Cibya Rahmawati; Yusuf Tri Herlambang (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2024)
Technological developments have a significant impact on users, technological advances can make it easier to collect all information. The presence of technology is used by various age groups, including teenagers, adults and children. Safeguarding children against the potential adverse effects of digital technology and social media necessitates parents with a profound comprehension of the ramifications of social media. The objective of this study is to impart insight into the significance of supervising children's utilization of digital technology. Employing the literature review approach, this research delves into pertinent articles related to the research title. The pivotal role played by parents remains crucial in shielding children from the detrimental impacts of digital technology.